Advances in different adult stem cell-derived exosomal non-coding RNAs for the treatment of neurological disorders: a narrative review - Ke, Lebin; Cao, Yingying; Lu, Zhiwei; Hallajzadeh, Jamal (Frontiers in Cell and Developmental Biology, 2024)
Neurological disorders are being increasingly recognized as major causes of death and disability around the world. Neurological disorders refer to a broad range of medical conditions that affect the brain and spinal cord. These disorders can have various causes, including genetic factors, infections, trauma, autoimmune reactions, or neurodegenerative processes. Each disorder has its own unique symptoms, progression, and treatment options. Optimal communication between interneurons and neuron-glia cells within the homeostatic microenvironment is of paramount importance. Within this microenvironment, exosomes play a significant role in promoting intercellular communication by transferring a diverse cargo of contents, including proteins, lipids, and non-coding RNAs (ncRNAs). Partially, nervous system homeostasis is preserved by various stem cell-derived exosomal ncRNAs, which include circular RNAs (circRNAs), long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and PIWI-interacting RNAs (piRNAs) (1). The diversity of these exosomal ncRNAs suggests their potential to influence multiple pathways and cellular processes within the nervous system.Stem cell-derived exosomes and their ncRNA contents have been investigated for potential therapeutic uses in neurological disorders, owing to their demonstrated capabilities in neuroprotection, neuroregeneration, and modulation of disease-related pathways. The ability of stem cell-derived exosomes to cross the blood-brain barrier makes them a promising delivery vehicle for therapeutic ncRNAs. This review aims to summarize the current understanding of different stem cell-derived exosomal ncRNAs and their therapeutic potential and clinical applications.